Relational Dialectics on Couples of Childbearing Age in Underprivileged Chinese Ethnicity Families in the Use of Contraception in Medan City - Hasyim Lbs, M. Akbar; Kurniawati, Dewi (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2023)
Dialectics in the form of contradictions in relationships which can occur due to various things and problems in couple life, as well as in determining the decision to carry out a family planning (KB) program or in determining the use of contraception. This research aims to analyze how the condition of internal and external dialectics and the strategies for resolving internal and external dialectics on couples of childbearing ages in underprivileged families of Chinese ethnicity in Medan City. The research approach uses a combined approach with a mixed methods model embedded design in data collection techniques and data analysis techniques. Therefore, the data produced is quantitative data to answer the internal and external dialectical condition, and qualitative data to answer strategies for resolving internal and external dialectics. Researcher prioritize quantitative data obtained from 100 respondents, while qualitative data collected through focus group discussion with 6 resource persons as informants are meant to complement the data and elaborate the analysis results more fully. The results of the study based on quantitative data with descriptive statistical analysis showed the condition of internal dialectic variables obtained an average value of 4.10 and the external dialectic variables obtained an average value of 3.49 on a 5-point Likert Scale. Based on the assessment criteria using the grand mean analysis, both are in a relatively stable condition. However, this value means that the respondents in this study tend to be more able to cope with the internal dialectics which occur than the external dialectics of contraceptive use. Meanwhile, the dialectic resolution strategy used by respondents in resolving internal dialectics tends to use a balance strategy and in resolving external dialectics using an integration strategy.